Contribuição dos painéis de alvenaria na análise de pórticos de concreto armado - Silva, Liriane Reis da (2014)
In this paper, a study on masonry infilled reinforced concrete (RC) frames subjected to service limit state horizontal loads is presented, considering the masonry panel contribution in the stiffness of the structure. The analysis of infilled frames is performed in two ways: using the equivalent diagonal strut concept, called here as macromodelling and the finite element method (FEM) for the micromodelling. Due to simplicity, equivalent strut models are really attractive for the inclusion of masonry panels in structural models of buildings frames. However, formulations available in the literature provide substantially distinct values for determining the axial rigidity of the equivalent strut, and disregarding some important parameters of the structural behavior of the infilled frame. In the FEM analysis, numerical simulations of infilled RC frames are done, with and without openings, with different spans, stiffness of the columns and masonry properties, using finite elements type shell in the modeling, in addition to the consideration of the contact frame-masonry. The simulations results allow the assessment of the limitations of the existing formulations for determining the width of the diagonal strut. In infilled frames with openings of doors and windows, is evaluated how the size and position of the aperture affects the stiffness of the structure. Finally, the maximum stresses (tensile, compression and shear) of all models are evaluated and compared with their respective resistant stresses in order to determine the possibility of cracking of the masonry panels of frames subjected to service limit state actions.